Experimental Study on Mudstone’s Strength Characteristics in Deep-Buried Coal-Measure Formation: A Case Study of Permian Longtan Formation - Ke Li; Weijian Yu; Youlin Xu; Long Lai; Hui Zhang; Mengtang Xu; Ze Zhou (Shock and Vibration)
To investigate the strength characteristics of mudstone in deep-buried coal-measure formation, four types of experiments have been conducted: (i) the X-ray diffraction (XRD) test; (ii) the scanning electron microscope (SEM) scanning test; (iii) the point load strength index test; and (iv) the uniaxial compressive strength test. It was concluded that the mudstone of the deep-buried coal measures in the Longtan Formation is dominated by chlorite, quartz, and albite using the XRD test, of which chlorite is primary, accounting for 74.3%. It was found that the three minerals in the mudstone are unevenly distributed using the SEM scanning test, albite is irregularly distributed in chlorite, and quartz is present in the albite and chlorite. Sixty-five specimens were tested for the point load strength index. After processing the data using the method suggested by the International Society for Rock Mechanics and Rock Engineering(ISRM), it was found that the maximum value of Is(50) was 6.10 MPa, the minimum is 0.14 MPa, and 53% of the specimens’ Is(50) values are below 2.0 MPa. The RMT-150C rock mechanics testing machine was used to conduct uniaxial compression tests on six specimens. The maximum uniaxial compressive strength (UCS) value is 59.26 MPa, the minimum value is 31.77 MPa, and the average is 45.64 MPa. Linear fitting and logarithmic fitting are carried out for the correlation between UCS and Is(50). The goodness of fit R2 of the linear fitting is 0.863, and that of the logarithmic fitting is 0.919, indicating a strong correlation between them. When it is challenging to make standard specimens, Is (50) can be used to estimate UCS.